Cement-free activating adhesives for construction applications
Through the slag-based adhesive system without Portland cement, the use of slag-based adhesive activated slag-based adhesive combined with calcium hydroxide and calcium sulfonate, the energy consumption and emission problems of traditional adhesives are solved, achieving high Hard strength and durability provide environmentally friendly building materials solutions.
Patent Information
- Application Number
- CN202380037060.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-28
- Filing Date
- 2023-04-28
- Publication Date
- 2024-12-17
AI Technical Summary
The existing building adhesive compositions still use Portland cement, resulting in increased energy consumption and carbon dioxide emissions, and insufficient strength and durability of the adhesive, making it difficult to completely replace traditional adhesives.
Using a slag-based adhesive system without Portland cement, through the combination of slag and alkaline activated components, slag lime is used to replace white Portland cement, combining calcium hydroxide and calcium sulfonate as slag accelerator to form Environmentally friendly adhesive.
High hard strength and early strength development without cement-free adhesives are achieved, reducing carbon footprint, and providing sustainable building materials applications to meet the durability requirements of building materials.
Smart Images

Figure BDA0005106076540000131 
Figure BDA0005106076540000141 
Figure BDA0005106076540000151
Abstract
Description
Technical Field
[0001] The present invention relates to building materials, and more particularly to cement-free activated adhesives for use in building materials. Background Art
[0002] Portland cement is widely used in adhesive compositions in the construction industry, and adhesive compositions are used to prepare cementitious compositions, and cementitious compositions are used to manufacture products that connect tiles, masonry and other types of building materials together, fill joints and gaps between materials, etc. This type of cement is a hydraulic cement, which is usually produced by heating limestone and clay minerals, which are finally ground into a fine powder form. The low cost and wide availability of the ingredients used to make portland cement make portland cement a cost-effective material, which is usually used to produce concrete, mortar, grouting, plaster, blocks, etc. However, the production of portland cement requires a large amount of energy consumption and emits a large amount of carbon dioxide (CO2) and many other pollutants. Each 1 ton of portland cement product produced may emit up to 1 ton of carbon dioxide.
[0003] In terms of reducing the carbon footprint of Portland cement, the use of geopolymers or pozzolans has been introduced into the manufacture of cementitious binder compositions, whereby a portion of the Portland cement is replaced by one of these environmentally friendly materials. For example, compositions have been developed that partially replace Portland cement with geopolymer substitutes (such as fly ash or slag), which are byproducts of other industries and originally ended up in landfills. Fly ash is a waste byproduct of thermal power plants, while slag is a waste byproduct of blast furnaces in the ironmaking industry (i.e., an industrial byproduct of the steelmaking process). In these modified binder compositions, the geopolymer substitute only replaces a portion of the Portland cement, so that the composition comprises geopolymer and Portland cement. The addition of Portland cement provides a resulting composition with hydraulic strength properties.
[0004] Known adhesive compositions still use a certain amount of Portland cement in their formulations, and due to the need to continue to produce Portland cement, energy use and CO2 emissions continue to rise. In view of the above, there is still a need for new and improved construction adhesive compositions that avoid the use of Portland cement while still maintaining the adhesive strength (i.e., hydraulic strength) and overall durability of the final products made using such adhesive compositions (e.g., concrete, mortar, thin-set adhesives (thin-bed mortars), grouts, self-leveling liners, patching compounds, plasters, blocks and other cementitious building materials), and the present invention provides a solution to this problem. Summary of the invention
[0005] In view of the problems and deficiencies of the prior art, an object of the present invention is to provide a cement-free adhesive composition, particularly a Portland cement-free adhesive composition suitable for use in products and applications that generally use or require cementitious adhesives and / or materials.
[0006] Another object of the present invention is to provide a cement-free adhesive composition which is environmentally friendly and reduces CO2 emissions during its manufacture.
[0007] Another object of the present invention is to provide cement-free adhesive compositions suitable for use in the manufacture of end products including mortars, thin-set adhesives, grouts, self-leveling liners, concretes, patching compounds, etc., as well as to provide such end products themselves.
[0008] Other objects and advantages of the invention will in part be obvious and will in part be apparent from the description. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] The features of the invention which are believed to be novel and the characteristic elements of the invention are particularly set forth in the appended claims. The drawings are for illustrative purposes only and are not drawn to scale. However, the invention itself as to its organization and method of operation may best be understood by reference to the following detailed description taken in conjunction with the accompanying drawings, in which:
[0010] Figure 1 is a comparative table comparing the prior art slag-based binder with the slaked lime activated slag-based binder of the present invention.
[0011] Figure 2 To display based on Figure 1 A table of comparative thin-film adhesives of the adhesive formulation products shown.
[0012] Figure 3A-3D Depicted are the plotted results of a three-level study conducted to determine the optimum replacement amount of slaked lime.
[0013] FIG. 4A depicts a graph of 1-day compressive strength of a prior art comparative sample containing WPC.
[0014] Figure 4B A graph depicting the 1-day compressive strength of the hydrated lime slag based binder of the present invention without WPC is shown.
[0015] FIG. 5A depicts a graph of 7-day compressive strength of a prior art comparative sample containing WPC.
[0016] Figure 5B A graph depicting the 7-day compressive strength of the hydrated lime slag based binder of the present invention without WPC is shown.
[0017] FIG. 6A depicts a graph of 28-day compressive strength of a prior art comparative sample containing WPC.
[0018] Figure 6B A graph depicting the 28 day compressive strength of the hydrated lime slag based binder of the present invention without WPC is shown.
[0019] Figure 7A- Figure 7B Graphs depicting the percentage usage of water for prior art samples containing WPC and samples of the present invention without WPC are shown, respectively.
[0020] Figure 8A- Figure 8B The plotted results of Figures 7A-7B are depicted separately, showing comparative plot trends.
[0021] Figure 9A- Fig. 9B Graphs depicting the solidification rate of a prior art sample containing WPC compared to a sample of the present invention without WPC are shown respectively. DETAILED DESCRIPTION
[0022] In describing the preferred embodiments of the present invention, reference will be made herein to the accompanying drawings. Figures 1 to 9B , like reference numerals in the accompanying drawings represent like features of the invention.
[0023] Embodiments of the present invention may include, consist of, or consist essentially of the features and steps described herein, as well as additional or optional additional ingredients, components, steps, or limitations described herein or otherwise understood by one skilled in the art. It should be understood that, unless otherwise stated, all concentrations disclosed herein are weight percent (wt.%) based on the total weight of the prepared composition or formulation.
[0024] Various embodiments of the present invention provide cement-free adhesives, particularly adhesives without Portland cement suitable for use in construction and building materials. In one or more embodiments, the present invention avoids the use of Portland cement by providing a slag-based adhesive system, which utilizes a combination of slag as a main adhesive component with a slag accelerating component and an alkaline activation component. Although known adhesive systems may include a combination of a slag component with a slag accelerating component, such systems also include the use of white Portland cement (WPC) as an alkaline activation component. The present invention relates to one or more cement-free adhesives that avoid the use of WPC to reduce its harmful effects.
[0025] According to the present invention, a cement-free adhesive is provided, which eliminates the need for cement (particularly Portland cement) by combining slag activated by an alkaline activation component with a slag acceleration component without using Portland cement. In this case, the cement-free adhesive system of the present invention is more environmentally friendly than traditional cementitious adhesive materials because they utilize the waste byproduct slag that would otherwise be disposed of in a landfill, and avoid the use of Portland cement, thereby reducing the CO2 emissions produced by its manufacture. The additional benefits of the cement-free adhesive of the present invention include its availability and performance. It has been found that traditional adhesives that include a combination of slag and cement (Portland cement or WPC) in a formulated product generally have problems associated with setting time and limited early strength development. It has also been found that the alkali activators used in these traditional formulated products, such as caustic NaOH, silicate Na2SiO2 or sulfate CaSO4, cause the adhesive to set too quickly, undesirably reducing the workable time (even if the setting strength time increases), or alternatively setting too slowly, providing enough workable time, but hindering early strength development.
[0026] The adhesive formulation of the present invention provides a cement-free adhesive comprising a combination of slag (instead of Portland cement) with a slag accelerator (which includes at least calcium hydroxide and a calcium salt) and an alkaline slag activator (which includes slaked lime, in place of Portland cement or WPC). In one or more embodiments, the cement-free adhesive formulation of the present invention comprises slag as the main adhesive component in an amount ranging from about 90-98% by weight, with the remaining about 2-10% by weight of the adhesive formulation comprising a combination of slaked lime (Ca(OH)2) as an alkaline slag activator and a slag accelerator comprising at least a combination of calcium hydroxide and a calcium salt, wherein the weight percentages (wt.%) are based on the total weight of the adhesive formulation. It has been found that the resulting lime-activated slag-based adhesive of the present invention has sufficient hydraulic strength, and the setting of the adhesive of the present invention achieves ease of use and early strength development suitable for building material applications. In particular, the cement-free lime-activated slag-based adhesive of the present invention has been found to be suitable for use as construction building materials, including but not limited to tile adhesives, mortars, thin-set mortars, self-leveling underlayments, thin-set adhesives, grouts, patching agents and other cementitious building materials.
[0027] In more detail, in one or more embodiments, the present invention relates to a slaked lime activated slag based binder formulation product that does not contain Portland cement (i.e., a Portland cement-free binder). The binder formulation product includes a combination of a primary binder component with a secondary binder component and an accelerator. The primary binder component is a geopolymer, preferably slag, which is activated by a secondary binder using a slag accelerator. In one or more embodiments, the primary binder includes a bulk slag selected from the following: granulated ground blast furnace slag (GGBFS) (also known as BFS granulated blast furnace slag), blast furnace slag, 120 type slag, iron metal slag and finely ground GGBFS (ground into fine powder) (manufactured by Holcim and sold under the trade name NewCem).
[0028] The secondary binder is selected from binders that can interact with and activate the slag primary binder component. Preferably, the secondary binder is slaked lime, which comprises Ca(OH)2 (calcium hydroxide), calcium-magnesium hydroxide, dolomite slaked lime, dolomite calcium hydroxide, >50% calcium hydroxide or >35% magnesium hydroxide. Exemplary slaked lime comprises S-type slaked lime or N-type slaked lime. The use of slaked lime as an activating component avoids the use of traditional caustic compounds and liquid silicates, provides sufficient workability time, avoids early strength development, forms a stable hydrated phase, and is generally environmentally friendly.
[0029] Slag and slaked lime are combined with a slag accelerator component that can interact with the slag. In one or more embodiments, the slag accelerator comprises a composition comprising at least a combination of calcium hydroxide and a calcium salt. In various preferred embodiments, the slag accelerator comprises a combination of calcium hydroxide and calcium disulphamate (calcium disulphamate) (calcium sulfamate), and optional additional ingredients. In these embodiments, it has been found that the combination of calcium hydroxide and calcium disulphamate is particularly suitable for interacting with the slag component and activating the slag component, providing the slag with increased hydraulic strength. In one or more embodiments, the slag accelerator can comprise at least about 10-60% by weight of calcium disulphamate and 1-20% by weight of calcium hydroxide. It has been found that a suitable slag accelerator is manufactured by BASF and sold under the trade name Hycon A 7600F.
[0030] According to one or more embodiments, the slaked lime activated slag-based adhesive of the present invention can be mixed together to form a premixed adhesive for addition with other chemical compounds to provide various construction building materials or final products (e.g., tile adhesives, mortars, thin-set mortars, self-leveling pads, thin-set adhesives, grouts, patching agents, etc.). Alternatively, the ingredients in the slaked lime activated slag-based adhesive of the present invention can be directly combined with other chemical compounds individually to provide various building materials.
[0031] In those embodiments directed to a premixed slag-based binder per se (i.e., a binder that is added with other components / ingredients / compounds to provide a building end product), the ratios of the ingredients may range from: the slag primary binder component is present in the premixed binder in an amount ranging from about 90-98 weight percent; slaked lime is present in an amount ranging from about 1-9 weight percent; and calcium hydroxide / calcium salt is present in an amount ranging from about 1-9 weight percent, wherein the weight percentages are based on the total weight of the premixed slag-based binder.
[0032] In an alternative embodiment of the present invention, a separate slag-based binder component of the present invention may be provided in a building end product in the range of about 15-50 wt. % slag component, about 1-20 wt. % hydrated lime component, and about 0.25-5 wt. % slag accelerator, based on the total weight of the end product formulation, with the remainder comprising various materials used to construct the specific building end product. It should be understood that in such end product formulations, the amount of slag to hydrated lime activator to calcium hydroxide / calcium salt accelerator is maintained in the range of 90-98 wt. % slag to 1-9 wt. % hydrated lime to 1-9 wt. % slag accelerator relative to the weight percentage of the slag-based binder formed from the mixture.
[0033] In those embodiments of the present invention, various additional materials can be added to the lime activated slag binder composition of the present invention to provide a final formulation product with one or more desired qualities for providing a building final product as discussed herein, in the case where the binder component of the present invention is mixed with a material to provide a building final product. For example, various formulations can include performance additives in combination with the slag binder of the present invention. The performance additive can include a dispersible powder polymer, which is present in an amount equal to or greater than 0% by weight to 10% by weight (preferably 1-10% by weight). For example, a suitable dispersible powder copolymer can be a powdered vinyl acetate ethylene copolymer (e.g., Vinnapas 5010N or Vinnapas 5044N manufactured by WackerChemie AG).
[0034] One or more rheology modifier additives may also be optionally included in various formulations, each in an amount ranging from equal to or greater than 0% to 1% by weight (preferably 0.01-1% by weight). Rheology modifiers may include cellulose ethers, such as materials designed for gelling materials, modified hydroxypropyl methylcellulose ethers, hydroxypropyl ethylcellulose ethers, and the like. Exemplary cellulose ethers may include cellulose ethers (e.g., manufactured by Dow and sold under the trade name Walocel 254), modified hydroxypropyl methylcellulose ethers (e.g., manufactured by Dow and sold under the trade name Walocel MK 3000PF) and / or hydroxypropyl ethylcellulose ethers (e.g., manufactured by Dow and sold under the trade name Walocel MKX 70000PP 01). Another rheology modifier may include a viscosity modifier based on diituan gum (e.g., Kelco-crete DG-F or Kelcocrete DG manufactured by CP Kelco).
[0035] Water reducer can be added to various formulations with an amount equal to or greater than 0 % by weight to 1 % by weight, preferably 0.01-1 % by weight, to enhance product flow or fluidity. Suitable water reducer / flow additives include superplasticizers, such as polycarboxylate ethers, melamine sulfonates, naphthalene sulfonates and / or lignin sulfonates (e.g., Compac 149S manufactured by Imerys SA, Melflux 2561 or Melflux 6681 manufactured by BASF, Lomar D manufactured by GEO, etc.). Optionally, one or more defoamers can also be added to various formulations of the present invention with an amount equal to or greater than 0 % by weight to 1 % by weight, preferably 0.01-1 % by weight, based on the gross weight of such formulations. Suitable defoamers can include hydrocarbons on inorganic carriers and powder additives of polyethylene glycol (e.g., Agitan P809 manufactured by Münzing Corporation).
[0036] Different aggregates may also be added to the various formulations of the present invention. For example, limestone, such as 325 mesh crushed limestone (e.g., Dolocron 45-12 manufactured by Prospector) may be added in an amount equal to or greater than 0% by weight to 10% by weight. Fine sand may be added to medium sand (e.g., 100 to 50 mesh sand) or even coarse sand (e.g., 35 mesh sand) in an amount ranging from 30-70% by weight and variations therebetween.
[0037] Optionally, one or more additional accelerating components may be added to various building final product formulations made according to the present invention. These additional accelerators may be added alone or in various combinations thereof, each in an amount ranging from equal to or greater than 0 wt % to 10 wt %, preferably 0.01-10 wt %, based on the total weight percentage of such resulting final product formulations. Suitable additional accelerating materials include, but are not limited to, sodium silicate, sodium hydroxide, sodium carbonate, potassium silicate, potassium hydroxide, potassium carbonate, organic calcium salts (e.g., calcium acetate, calcium formate, calcium sulfamate, etc.), calcium sulfate (e.g., gypsum, including (anhydrous, hemihydrate and dihydrate types)), and the like.
[0038] Again, the Portland cement alkali-free activated slag-based adhesive of the present invention can be a premixed composition that is added to other ingredients when manufacturing building materials or final products, or alternatively, the various components of the slag-based adhesive of the present invention can be added separately when formulating such building material final products. The present invention covers various building material final product formulations that incorporate the slag-based adhesive of the present invention. In one or more embodiments, the final product formulations may include, but are not limited to, tile adhesives, mortars, thin-patch mortars, self-leveling pads, thin-patch adhesives, grouts, patching agents, and the like.
[0039] According to one or more embodiments, the present invention relates to a tile adhesive (thin-layer adhesive) formulation product, which comprises slag in an amount of about 15-50 wt%, slaked lime in an amount of about 1-20 wt%, and a slag accelerator in an amount of about 0.25-5 wt% (preferably a slag accelerator comprising calcium hydroxide and calcium diaminosulfonate). Based on the total weight of the tile adhesive formulation product, the adhesive formulation product may also include: a redispersible powdered vinyl acetate ethylene copolymer in an amount of equal to or greater than 0 wt% to 10 wt%; a cellulose ether in an amount of equal to or greater than 0 wt% to 1 wt% (preferably 0.01-1 wt%); limestone (preferably crushed aggregate) in an amount of equal to or greater than 0 wt% to 10 wt% (preferably 1-10 wt%); and sand (aggregate) in an amount of about 40-70 wt%.
[0040] An alternative embodiment of the present invention relates to a mortar bed formulation product, which comprises slag in an amount of about 15-50 wt%, slaked lime in an amount of about 1-20 wt%, a slag accelerator in an amount of about 0.25-5 wt% (preferably a slag accelerator comprising calcium hydroxide and calcium diaminosulfonate), a dispersible powder copolymer in an amount of equal to or greater than 0 wt% to 10 wt% (preferably 1-10 wt%), a cellulose ether in an amount of equal to or greater than 0 wt% to 1 wt% (preferably 0.01-1 wt%), limestone in an amount of equal to or greater than 0 wt% to 10 wt% (preferably 1-10 wt%) (preferably 325 mesh crushed aggregate), and sand in an amount of about 40-70 wt% (preferably 35 mesh coarse sand), based on the total weight of the mortar bed formulation product.
[0041] Embodiments of the present invention also relate to self-leveling underlayment (SLU) materials or formulated products. In these embodiments, the SLU may include slag in an amount of about 15-50 wt%, slaked lime in an amount of about 1-20 wt% (preferably S-type slaked lime, N-type slaked lime), and slag accelerator in an amount of about 0.25-5 wt% (preferably a slag accelerator comprising calcium hydroxide and calcium diaminosulfonate (e.g., Hycon A 7600F)). The SLU may also include, based on the total weight of the tile adhesive formulation, a redispersible powdered ethyl acetate ethylene copolymer as a performance additive in an amount of equal to or greater than 0 wt % to 10 wt % (preferably 0.01-10 wt %); a cellulose ether as a first rheology modifier in an amount of equal to or greater than 0 wt % to 1 wt % (preferably 0.01-1 wt %); a viscosity modifier based on dithiocarbamide as a second rheology modifier in an amount of equal to or greater than 0 wt % to 1 wt % (preferably 0.01-1 wt %); a water reducer, a flow additive, such as a superplasticizer, in an amount of equal to or greater than 0 wt % to 1 wt % (preferably 0.01-1 wt %); a defoamer, such as a powdered additive of hydrocarbons and polyethylene glycol on an inorganic carrier, in an amount of equal to or greater than 0 wt % to 1 wt % (preferably 0.01-1 wt %); and sand (fine to medium aggregate) in an amount of about 30-70 wt %.
[0042] Optionally, the SLU of the present invention may further comprise one or more additional accelerating components, which may be added alone or in various combinations thereof, with the amount of each component ranging from equal to or greater than 0 wt % to 10 wt %, preferably 0.01-10 wt %. Exemplary suitable additional accelerating components include sodium silicate, sodium hydroxide, sodium carbonate, potassium silicate, potassium hydroxide, potassium carbonate, organic calcium salts, calcium sulfate, and the like.
[0043] Another embodiment of the present invention includes a grout formulation comprising slag in an amount of about 15-50 wt%, slaked lime in an amount of about 1-20 wt% (preferably S-type slaked lime, N-type slaked lime), and a slag accelerator in an amount of about 0.25-5 wt% (preferably a slag accelerator comprising calcium hydroxide and calcium diaminosulfonate (e.g., Hycon A 7600F)). Based on the total weight of the tile adhesive formulation, the grout may further include: a dispersible powder copolymer (e.g., a powder copolymer having hydrophobic properties) as a performance additive in an amount of equal to or greater than 0 wt% to 10 wt% (preferably 0.01-10 wt%); a cellulose ether as a first rheology modifier in an amount of equal to or greater than 0 wt% to 1 wt% (preferably 0.01-1 wt%); a viscosity modifier based on dithiocarbamide as a second rheology modifier in an amount of equal to or greater than 0 wt% to 1 wt% (preferably 0.01-1 wt%). 0.01-1 wt %); water reducing agent, flow additive, such as superplasticizer, its amount is equal to or greater than 0 wt % to 1 wt % (preferably 0.01-1 wt %); defoamer, such as those described herein, its amount is equal to or greater than 0 wt % to 1 wt % (preferably 0.01-1 wt %); limestone (preferably 325 mesh crushed aggregate) is equal to or greater than 0 wt % to 10 wt % (preferably 1-10 wt %); and sand (fine to medium aggregate) is about 30-70 wt %. The grouting formulation product may also optionally include one or more additional accelerating components as described herein, each of which is in an amount ranging from equal to or greater than 0 wt % to 10 wt %, preferably 0.01-10 wt %.
[0044] The present invention also relates to a patch formulation product, which comprises slag in an amount of about 15-50% by weight, slaked lime in an amount of about 1-20% by weight (preferably S-type slaked lime, N-type slaked lime), and a slag accelerator in an amount of about 0.25-5% by weight (preferably a slag accelerator comprising calcium hydroxide and calcium diaminosulfonate (for example, Hycon A 7600F)). The repair agent formulation product may also include: a dispersible powder copolymer (e.g., a powder copolymer with hydrophobic properties) as a performance additive, in an amount equal to or greater than 0 wt% to 10 wt% (preferably 0.01-10 wt%); a cellulose ether as a first rheology modifier, in an amount equal to or greater than 0 wt% to 1 wt% (preferably 0.01-1 wt%); a viscosity modifier based on dithiocarbamide as a second rheology modifier, in an amount equal to or greater than 0 wt% to 1 wt% (preferably 0.01-1 wt%); a water reducer, a flow additive, such as a superplasticizer, in an amount equal to or greater than 0 wt% to 1 wt% (preferably 0.01-1 wt%); and a defoamer, such as those described herein, in an amount equal to or greater than 0 wt% to 1 wt% (preferably 0.01-1 wt%). Based on the total weight of the tile adhesive formulation, the patch formulation comprises: limestone (preferably crushed limestone) in an amount equal to or greater than 0 wt% to 10 wt% (preferably 1-10 wt%); and sand (fine to medium aggregate (5000-7000 microns)) in an amount of about 30-70 wt%. The grout formulation may also optionally comprise one or more additional accelerating components as described herein, each in an amount ranging from equal to or greater than 0 wt% to 10 wt%, preferably 0.01-10 wt%.
[0045] Although not intended to be limiting, various exemplary thin-patch adhesive formulations of the present invention comprising the present Portland cement-free alkali-activated slag-based adhesives were prepared and compared to known slag-based adhesives having Portland cement (particularly white Portland cement "WPC") as an activator. As described herein, the slag-based adhesives of the present invention are free of Portland cement, making them cement-free adhesives whereby the Portland cement component has been entirely replaced with hydrated lime. See Figure 1-2 , Figure 1 Table depicting different formulations of known Portland cement-based / slag-containing binders (denoted as "PA" in the table) compared to the slaked lime activated slag-based binders of the present invention (denoted as "Inv." in the table), which contain S-type slaked lime as a WPC replacement, acting as an activator. Alkaline slaked lime increases the pH of the mixture, enhances the dissolution of the amorphous phase of the slag and promotes the hydration reaction of the slag. These different comparative formulations were used to make Figure 2 The different comparative thin-film adhesive samples are shown in the table shown in .
[0046] The powdered form was prepared in 2000 g batches. Figure 2 Comparative test samples of , where the individual ingredients were weighed in a 1 gallon bucket and mixed in a paint shaker for 2 minutes and 30 seconds at least one day before the test. The powdered samples contained different comparative slag-based binders and ASTM grade sands in a ratio of 1 part binder to 2.75 parts sand, as specified in ASTM C109-11. Water was added to the various powdered samples, and an electric drill equipped with a paddle mixer was used to mix the samples for sixty seconds, then matured for ninety seconds, and finally mixed for another sixty seconds, trying to replicate the mixing time described in ASTM C109. After mixing, the mixed samples were then placed directly into the flow table for flow testing according to ASTM C109. The samples were flow tested, and six 2in x 2in compressive strength cube samples were produced and cured, and a 4oz cup was filled to test the setting time using an automatic Vicatronic Automatic Vicat reader, and the setting measurements were recorded after a 120-150 minute delay, with 41 samples taken every 10 minutes, for a total of 530-560 minutes.
[0047] refer to Figures 3A-3D To determine the amount of slaked lime replacement for WPC in the present invention, a three-stage study was conducted testing several different ratios of slag, accelerator and activator, using OPC and S-type slaked lime as the activator. Figure 3A Highlight areas of interest for tertiary studies, and Figure 3B Depicted are the positions of the ternary compositions of the comparative adhesives tested and the ratios recommended via the ThinPatch formulation product from BASF. Figure 3C and 3D Describe the adhesive containing the prior art WPC ( Figure 3C ) and the Portland cement-free slaked lime activated adhesive of the present invention ( Figure 3D ). Of these studies, only seventeen (17) samples were tested because three (3) of the samples (i.e., Samples 1, 3, and 8) were used for the WPC and hydrated lime binder activator studies because these formulations contained only HyCon A 7600F (hereinafter referred to as "HyCon") and slag or only slag.
[0048] The compressive stress of the tested comparative samples was measured at time intervals of 1 day ("1-D"), 7 days ("7-D"), and 28 days ("28-D"). Referring to the comparative 1-day compressive strength of Figures 4A and 4B, which depict graphs of prior art WPC-containing samples and the slaked lime slag-based binder of the present invention, it was found that increasing the percentage of slag accelerator (i.e., HyCon) significantly increased the compressive strength of all samples. It was found that the 1-D compressive strength of all samples with a percentage of HyCon above 2% was above 700 PSI, and the early strength of the samples without HyCon (i.e., Samples 1, 4, 10, 14, and 20) was very low, with no sample exceeding 252 PSI. Samples 2, 7, 12, and 17 had 1% HyCon A 7600F, which had strengths greater than the samples without HyCon, but had strengths below 500 PSI. The strengths of samples 5 and 15 with 2% HyCon were 736PSI and 928PSI, respectively, indicating a significant increase in strength at low percentage HyCon usage. The strengths of samples with HyCon percentages between 3% and 6% in the Portland cement series ranged from 1390PSI to 1610PSI, while the 1-D strengths of the slaked lime binder samples of the present invention within the same HyCon range reached 950PSI to 1440PSI. These results indicate that even at a dosage as low as 1%, HyCon has a significant effect on producing 1-D compressive strength, making it a very effective slag accelerator at low dosages.
[0049] Figures 5A and 5B depict graphs comparing 7-day compressive strength, respectively, while Figures 6A and 6B depict graphs comparing 28-day compressive strength, respectively. It was found that most samples containing HyCon performed better than samples without HyCon, and those samples with greater than 3% HyCon and slaked lime as activators (samples 16 and 19) produced sufficient strengths of 3180 PSI and 2920 PSI. The results show that the use of HyCon at low doses of 1% and 2% has a significant effect on early strength development compared to formulations without HyCon; however, the compressive strength development of these formulations is more comparable to formulations without HyCon at 7-D and 28-D. The 1D strength of samples containing HyCon in an amount exceeding 3% of the binder will increase significantly, far exceeding samples without HyCon, and even at 7-D and 28-D, its compressive strength exceeds that of samples without HyCon. Therefore, the use of HyCon in amounts exceeding 3% of the adhesive will increase the 28-D compressive strength of the adhesive compared to formulations containing no HyCon or containing a lower percentage of HyCon.
[0050] For the effect of alkaline activators on strength development at equal HyCon percentages (see Figure 2Graph), it has been found that in the test sample formulations with 1% HyCon and different slag to activator ratios, the slaked lime slag-based binders of the present invention (samples / formulations 12, 15 and 17) show improved compressive strength for 1-D, 7-D and 28-D strengths compared to the prior art WPC formulations (samples / formulations 2, 5 and 7). Based on these test samples, it has been found that the formulations / samples containing equal to or less than 3% HyCon provide greater strength than the prior art combined with WPC when combined with slaked lime (i.e., without WPC). For comparative formulations containing greater than 3% HyCon, the results are opposite (e.g., see formulations 6 and 16). Therefore, according to one or more embodiments of the present invention, various slaked lime slag-based binders can contain less than 3% HyCon in combination with slag and slaked lime. However, in other embodiments, the results still demonstrate that slaked lime as an effective alkaline activator provides sufficient 28-day compressive strength together with greater than 3% HyCon (e.g., see formulations 16 and 19). Based on the compressive strength studies, hydrated lime was found to be an effective replacement for WPC, especially in formulations containing 2% HyCon and below. However, although the strength of WPC formulations was higher at 3% HyCon and above compared to the hydrated lime slag-based binder of the present invention, it was still found that the compressive strength of the hydrated lime slag-based binder of the present invention at 3% HyCon and above provided sufficient 28-day compressive strength to make hydrated lime suitable for complete replacement of WPC in slag-based binders.
[0051] Referring to Figures 7A-7B, the percentage of water used to achieve the desired flow rate for a prior art WPC test sample is depicted compared to a test sample with a slaked lime slag-based binder. Figures 8A-8B show the plasticizing effectiveness of the prior art HyCon using WPC compared to the HyCon plasticizing effectiveness of the present invention using a slaked lime binder. The water used for each sample was determined based on the flow reading. It has been found that slaked lime is a suitable substitute for all WPCs in traditional binders because it can provide sufficient plasticizing effect. The graphs of Figures 8A and 8B show comparable chart trends of the percentage of HyCon and the percentage of water for the prior art formulations and the present invention formulations for comparison, with the slope of the points ranging from 0% to 3% HyCon being much steeper than the slope of the points ranging from 3% to 6% HyCon. Based on this data, it has been found that replacing WPC with the slag-HyCon-slaked lime binder of the present invention provides comparable results, with the maximum plasticizing effect detected at the 3% level of the binder, and thus similar viscosity and processability can be provided at the same percentage of water.
[0052] 9A and 9B depict the performance of a prior art WPC test sample ( FIG. 9A ) compared to a slaked lime slag based binder of the present invention ( FIG. 9B ) using an automated Vicat instrument. Fig. 9B ). The results show that the preforming effect of the formula products containing WPC and slaked lime is similar, the average initial setting time of the slaked lime adhesive is 251.2 minutes, and the average initial setting time of the WPC adhesive is 238.4 minutes. In addition, the setting time indicates a good processing time of 3-4 hours on average.
[0053] It has been found that the combination of slaked lime as an alkaline activator with slag and a slag accelerator (i.e., accelerating the strength development of slag) comprising calcium hydroxide and calcium diaminosulfonate forms an acceptable adhesive. That is, slaked lime is an acceptable substitute or alternative for WPC and can completely replace WPC in slag-based adhesives. In one or more embodiments, it is found that the adhesive of the present invention containing less than 3% slaked lime develops compressive strength earlier than the WPC sample / formulation product of the prior art. It is also found that the slaked lime slag-based adhesive of the present invention provides sufficient compressive strength at 7-D and 28-D, some exceeding 3000PSI. The present invention provides a cement-free slag-based adhesive, which is still suitable for providing an acceptable 1-D strength of 488PSI (i.e., sample 12) even when the amount of slag accelerator is as low as 1% of the adhesive. It has been found that the adhesive of the present invention is formulated with an adhesive without Portland cement to produce an acceptable building product (e.g., a cementitious product), thereby reducing carbon footprint and minimizing waste.
[0054] Although not intended to be limiting, as an exemplary embodiment, the thin-set tile adhesive of the present invention was formulated using the slaked lime slag-based adhesive of the present invention and compared to a prior art adhesive formulated using WPC (i.e., 253 Gold white manufactured by LATICRETE International, Inc.). Test comparison formulations of the tile adhesive of the present invention against a prior art Portland cement-containing adhesive using 253 Gold white and a Portland cement-free adhesive containing slag-HyCon-slaked lime are depicted below in Table 1. As shown, the present invention replaces white Portland cement and calcium formate with a slag accelerator containing calcium hydroxide and calcium diaminosulfonate (specifically HyCon A 7600F) and slaked lime, respectively.
[0055] Table 1: The following proportions of ingredients in the slaked lime slag based adhesive itself include, in weight % based on the total weight of the adhesive itself: 94.35% slag, 1.87% HyCon and 3.78% slaked lime. This slaked lime slag based adhesive replaces the adhesive system present in the prior art Portland cement containing adhesive using 253 Gold white at a ratio of 1:1. The prior art WPC based adhesive ("WPC") and the slag based adhesive (SBB) of the present invention are provided to a cementitious thin-set powder (particularly, 253 Gold manufactured by LATICRETE International, Inc., which is a polymer reinforced bagged cementitious thin-set powder) and mixed with water to form a thin-set adhesive for installing tile and / or stone.
[0056]
[0057]
[0058] Both formulations were tested according to the ANSI A118.4 Standard for Modified Dry Set Cement Mortar and the ANSI A118.11 Standard for EGP Modified Dry-set Mortar. The results are shown in Tables 2-4 below, which show the demonstrated shear strength results (Table 2), open time results (Table 3), and heliopath viscosity results (Table 4). Referring to Table 2, the shear strength measurements of the WPC-Prior Art ("WPC-PA") formulation and the SBB-Inventive / Inventive formulation ("SBB-Inv.") were compared to the ANSI A118.4 Shear Strength Standard for Different Days ("STD") . These results indicate that the shear strength of the tile adhesive (SBB) of the present invention exceeds the ANSI A118.4 and A118.11 standards, making it a suitable replacement or alternative to the WPC-Prior Art formulation. Table 3 shows that the tile adhesive (SBB) of the present invention also exceeds the ANSI A118.4 standard at 20 and 30 minutes of open time. In addition, referring to Table 4, when the percentage of water of the tile adhesive (SBB) of the present invention and the WPC-prior art ("WPC-PA") formulations is the same, both at 22.90 wt%, the formulations show almost the same viscosity. Therefore, these results demonstrate the feasibility of developing Portland cement-free products using the slag-HyCon-hydrated lime adhesive of the present invention as an alternative to Portland cement-based adhesives.
[0059] Table 2: ANSI A118.4 and ANSI A118.11 shear strength results.
[0060]
[0061] Table 3 : ANSI A118.4 Open Time Results.
[0062]
[0063]
[0064] Table 4: Heliopath viscosity results.
[0065]
[0066] Although the present invention has been specifically described in conjunction with specific preferred embodiments, it is apparent that many substitutions, modifications and variations will be clear to those skilled in the art in light of the foregoing description. It is therefore contemplated that the appended claims will cover any such substitutions, modifications and variations as long as they fall within the true scope and spirit of the present invention.
[0067] Having thus described the invention, what is claimed is:
Claims
1. A Portland cement-free adhesive formulation product for building materials, the adhesive formulation product comprising: a geopolymer material, said geopolymer material being present in an amount of about 90-98% by weight of said adhesive formulation; an activator comprising slaked lime, said activator being present in an amount from greater than 0% to less than 10% by weight of said adhesive formulation, a slag accelerator comprising calcium hydroxide and a calcium salt, the slag accelerator being present in an amount from greater than 0% to less than 10% by weight of the adhesive formulation; The weight % is based on the total weight of the adhesive formulation.
2. A Portland cement-free adhesive formulation product for building materials, the adhesive formulation product comprising: a slag material, the slag material being present in an amount of about 90-98% by weight of the adhesive formulation; an activator comprising slaked lime, said activator being present in an amount of about 1 to 9% by weight of said adhesive formulation, a slag accelerator comprising calcium hydroxide and a calcium salt, the slag accelerator being present in an amount of about 1-9% by weight of the adhesive formulation; The weight % is based on the total weight of the adhesive formulation.
3. The binder of claim 2, wherein the slag comprises bulk slag selected from the group consisting of ground granulated blast furnace slag (GGBFS), blast furnace slag, type 120 slag, iron metal slag, and finely ground GGBFS.
4. The adhesive of claim 2, wherein the hydrated lime activator comprises calcium hydroxide, calcium-magnesium hydroxide, dolomite hydrated lime, dolomite calcium hydroxide, >50% calcium hydroxide or >35% magnesium hydroxide, S-type hydrated lime or N-type hydrated lime.
5. The adhesive of claim 2, wherein the slag accelerator comprises at least a combination of calcium hydroxide and calcium diaminosulfonate.
6. The binder of claim 5, wherein the calcium hydroxide is present in an amount of 1-20 wt% and the calcium diaminosulfonate is present in an amount of 10-60 wt% based on the total weight of the slag accelerator.
7. The adhesive of claim 2, wherein the adhesive formulation is mixed with one or more additional compounds for use in providing a building material composition.
8. An adhesive as claimed in claim 7, wherein the adhesive formulation comprises a pre-mixed hydrated lime activated slag based adhesive for addition with one or more additional compounds.
9. The adhesive as claimed in claim 7, wherein the provided building material composition is selected from the group consisting of tile adhesives, mortars, thin-set mortars, self-leveling underlayments, thin-set adhesives, grouts, patching agents and other cementitious building materials.
10. The adhesive of claim 7, wherein the slag material is present in an amount of about 15-50 wt % of the building material composition; the activator is present in an amount of about 1-20 wt % of the building material composition; and the slag accelerator is present in an amount of about 0.25-5 wt % of the building material composition, wherein the wt % is based on the total weight of the building material composition.
11. The adhesive of claim 7, wherein the one or more additional compounds are selected from the group consisting of a dispersible powder copolymer, one or more rheology modifier additives, a water reducer, one or more defoamers, limestone, sand, and one or more additional accelerators.
12. The adhesive of claim 11, wherein the one or more additional compounds comprises a dispersible powder copolymer present in an amount equal to or greater than 0% to 10% by weight.
13. The adhesive of claim 11, wherein the one or more additional compounds include one or more rheology modifier additives present in an amount equal to or greater than 0 wt. % to 1 wt. %.
14. The adhesive of claim 13, wherein the one or more rheology modifiers include cellulose ethers, materials designed for gelling materials, modified hydroxypropyl methylcellulose ethers, hydroxypropyl ethylcellulose ethers, and dimethicone-based viscosity modifiers.
15. The adhesive of claim 11, wherein the one or more additional compounds comprises a water reducer present in an amount equal to or greater than 0 wt. % to 1 wt. %.
16. The adhesive of claim 13, wherein the water reducing agent comprises a superplasticizer selected from the group consisting of polycarboxylate ethers, melamine sulfonates, naphthalene sulfonates, and / or lignin sulfonates.
17. The adhesive of claim 11, wherein the one or more additional compounds comprises limestone present in an amount equal to or greater than 0 wt% to 10 wt%.
18. The adhesive of claim 11, wherein the one or more additional compounds include sand present in an amount ranging from 30-70 wt%.
19. The adhesive of claim 11, wherein the one or more additional compounds include one or more additional accelerators present in an amount equal to or greater than 0 wt. % to 10 wt. %.
20. The adhesive of claim 19, wherein the one or more additional compounds are selected from the group consisting of sodium silicate, sodium hydroxide, sodium carbonate, potassium silicate, potassium hydroxide, potassium carbonate, organic calcium salts including calcium acetate, calcium formate, calcium sulfamate, and calcium sulfate.
21. A Portland cement-free tile adhesive or mortar composition comprising: a slag material, the slag material being present in an amount of about 15-50% by weight; an activator comprising slaked lime, the activator being present in an amount of about 1-20% by weight; a slag accelerator comprising calcium hydroxide and a calcium salt, the slag accelerator being present in an amount of about 0.25-5% by weight; a redispersible powdery vinyl acetate ethylene copolymer, wherein the amount of the redispersible powdery vinyl acetate ethylene copolymer is equal to or greater than 0 wt % to 10 wt %; Cellulose ether, the amount of the cellulose ether being equal to or greater than 0 wt % to 1 wt %; Limestone, the amount of the limestone being equal to or greater than 0 wt % to 10 wt %; as well as Sand, the amount of sand is about 40-70% by weight, All weight % are based on the total weight of the tile adhesive or mortar composition.
22. A Portland cement-free self-leveling liner composition comprising: a slag material, the slag material being present in an amount of about 15-50% by weight; an activator comprising slaked lime, the activator being present in an amount of about 1-20% by weight; a slag accelerator comprising calcium hydroxide and a calcium salt, the slag accelerator being present in an amount of about 0.25-5% by weight; a redispersible powdery vinyl acetate ethylene copolymer, wherein the amount of the redispersible powdery vinyl acetate ethylene copolymer is equal to or greater than 0 wt % to 10 wt %; a first rheology modifier of cellulose ether, wherein the amount of the first rheology modifier is equal to or greater than 0 wt % to 1 wt %; a second rheology modifier based on a viscosity modifier of diterpene gum, the second rheology modifier being in an amount of greater than or equal to 0 wt % to 1 wt %; Water reducing agent, flow additive; the amount of the water reducing agent, flow additive is equal to or greater than 0 weight % to 1 weight %; a defoaming agent, wherein the amount of the defoaming agent is equal to or greater than 0 wt % to 1 wt %; Sand, the amount of sand is about 30-70% by weight, All weight % are based on the total weight of the self-leveling pad composition.
23. The composition of claim 22, further comprising one or more additional accelerating components in an amount ranging from equal to or greater than 0% to 10% by weight.
24. A Portland cement-free grout or patch composition comprising: a slag material, the slag material being present in an amount of about 15-50% by weight; an activator comprising slaked lime, the activator being present in an amount of about 1-20% by weight; a slag accelerator comprising calcium hydroxide and a calcium salt, the slag accelerator being present in an amount of about 0.25-5% by weight; a redispersible powdery vinyl acetate ethylene copolymer, wherein the amount of the redispersible powdery vinyl acetate ethylene copolymer is equal to or greater than 0 wt % to 10 wt %; a first rheology modifier of cellulose ether, wherein the amount of the first rheology modifier is equal to or greater than 0 wt % to 1 wt %; a second rheology modifier based on a viscosity modifier of diterpene gum, the second rheology modifier being in an amount of greater than or equal to 0 wt % to 1 wt %; Water reducing agent, flow additive; the amount of the water reducing agent, flow additive is equal to or greater than 0 weight % to 1 weight %; a defoaming agent, wherein the amount of the defoaming agent is equal to or greater than 0 wt % to 1 wt %; Limestone, the amount of the limestone being equal to or greater than 0 wt % to 10 wt %; as well as Sand, the amount of sand is about 30-70% by weight, All weight % are based on the total weight of the grout or patch composition.
